Basic food microbiology - George J Banwart (Chapman and Hall, 1989)
The book discusses recent innovations in the use of microorganisms and fermentations to produce various foods; how to can make fuller use of fishery resources and recycled waste products; and the critical role that microbiology plays in ensuring the safety and quality of processed foods. Other key ares covered include loss prevention and responsible pest control, food preservation and its particular importance in developing countries, and aesthetic considerations of new food resources. The book is complemented by a wide range of charts, graphs, and illustrations